Cystatin B, cathepsin L and D related to surrogate markers for cardiovascular disease in children - Dencker, Magnus (Lund University, 2017)
Objective: This study investigated potential associations between novel biomarkers for
cardiovascular disease and other surrogate markers for health.
Methods: Community sample of 170 (92 boys and 78 girls) children aged 8-11 years. Total fat mass (TBF) and abdominal fat (AFM) were measured by Dual-energy x-ray absorptiometry (DXA). Total body fat was also expressed as percentage of total body mass (BF%), and body fat distribution was calculated as AFM/TBF. Maximal oxygen uptake (VO2PEAK), systolic and diastolic blood pressure (SBP and DBP) and pulse pressure (PP) were
measured. Echocardiography was performed. Left atrial size (LA) and left ventricular mass (LVM) were measured. A follow-up DXA scan was available in 152 children (84 boys and 68 girls). Frozen serum samples were analyzed for cystatin B, cathepsin L and cathepsin D.
Results: Partial correlations between cystatin B versus lnTBF, lnBF%, lnAFM, AFM/TBF,
VO2PEAK and PP were; r=0.38, 0.36, 0.38, 0.29, -0.25 and 0.25, P=0.001 or less for all. Weaker predominantly non-significant correlations were found for cathepsin L, whereas cathepsin D was not related to any surrogate markers for health. No significant correlations were found between biomarkers and change in body fat over 2 years.
Conclusion: Findings from this community-based cohort of young children show that
surrogate markers for cardiovascular disease such as total fat mass, percent body fat,
abdominal fat, body fat distribution, maximal oxygen uptake and pulse pressure were all associated with cystatin B. This was not found for cathepsin L or cathepsin D.

Purpose:

This study investigated potential associations between novel biomarkers for
cardiovascular disease (Cystatin B, cathepsin L and D9 and other surrogate markers for health.

Total fat mass (TBF) and abdominal fat (AFM) were measured by Dual-energy x-ray
absorptiometry (DXA). Total body fat was also expressed as percentage of total body mass (BF%), and body fat distribution was calculated as AFM/TBF. Maximal oxygen uptake (VO2PEAK), systolic and diastolic blood pressure (SBP and DBP) and pulse pressure (PP) were measured. Echocardiography was performed. Left atrial size (LA) and left ventricular mass (LVM) were measured. A follow-up DXA scan was available in 152 children (84 boys and 68 girls). Frozen serum samples were analyzed for cystatin B, cathepsin L and cathepsin D.

Studien studerade relationen mellan traditionella och nya riskfaktorer för hjärt-och kärlsjukdom som Cystatin B, cathepsin L and D hos barn. Totalt studerade 170 bran i åldern 8-11 år. Cystatin B var svagt-måttligt relaterat till kropps fett och kondition medan cathepsin L and D inte var det.

Syfte:

Studera relationen mellan traditionella och nya riskfaktorer för hjärt-och kärlsjukdom som Cystatin B, cathepsin L and D hos barn

Följande mätningar är gjorda; Blodtryck, Fysisk prestationsförmåga, Ekokardiografi, DXA, Blodprov analyserade för cystatin B, cathepsin L och cathepsin D.
Cystatin B, cathepsin L och D relaterat till andra riskfaktorer för hjärt-och kärlsjukdom hos barn
Keywords: Risk Factors; Riskfaktorer; Child; Barn; Cardiovascular Diseases; Kardiovaskulära sjukdomar; Cathepsin D; Katepsin D; Skinfold Thickness; Kroppsfettsmätning; Cystatin B; Cystatin B; Cathepsin L; Katepsin L; DEMOGRAPHY (POPULATION, VITAL STATISTICS, AND CENSUSES); DEMOGRAFI (POPULATION, VITALSTATISTIK OCH FOLKRÄKNINGAR); Medical and Health Sciences; Medicin och hälsovetenskap